Innovationism as legitimization. A critical perspective on discourses of innovation, knowledge-based economy, information society and others - Zarycki, Tomasz (Journal of Public Governance, 2014)
The paper presents an analysis of the genesis and functions of a wide range of modernization discourses on knowledge-based/knowledge-driven economy, innovative economy, or information society. Relying on the methods of critical discourse analysis (of what we call “discourses of the new society”, given their strong component of the vision of socio-cultural changes), it shows the basic mechanisms of legitimization of social inequalities and reproduction of hierarchies in the contemporary world. The paper uses the Wallerstein notions of the world system theory to focus on the role of the discourses in legitimization of the dependence of the peripheral and semi-peripheral countries.